Konseling Logoterapi Dalam Penetapan Tujuan Hidup Remaja Broken home - Jayanti, Nurani (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
This paper aims to reveal how logotherapy counseling in setting adolescent life goals is broken home, by having a meaningful life humans will find a directed life process, logotherapy counseling invites clients to understand the wisdom of each problem from the beginning of the counseling process. The method used is library research. It can be seen that with 4 steps logotherapy counseling is the stage of forming and fostering rapport, the stage of disclosure and assessment of problems, the stage of joint discussion, and the stages of evaluation and conclusion. The results obtained from the research data sources are that logotherapy counseling can help clients determine their life goals, clients who face fearsome difficulties or are in conditions that do not allow them to move and creativity are helped to find the meaning of their life in how they deal with these conditions and how his suffering. Logotherapy counseling teaches clients to see the positive value of suffering and provides an opportunity to feel grateful for the suffering and problems being experienced by the client